Effects of (−)-6,6′-dinitrohinokinin on adult worms of Schistosoma mansoni: A proteomic analyses - Magalhães, Lizandra G.; Lima, Thais C.; de Paula, Renato G.; Morais, Enyara R.; Aguiar, Daniela P.; Gardinassi, Luiz G.; Garcia, Gustavo R.; Laurentiz, Rosangela S.; Rodrigues, Vanderlei; Bastos, Jairo K.; Filho, Ademar A. S.; Yatsuda, Ana P.; et al. (Springer Nature, 2016)
Schistosomiasis, a chronic disease that affects million people worldwide, is caused by trematodeflukes of the genus Schistosoma. The lack of an anti-schistosomiasis vaccine and massive monother-apy with praziquantel reinforces the need for search and development of new therapeutic drugs.Recently, we demonstrated that the essential oil of Piper cubeba L., Piperaceae, and their derivative diben-zylbutyrolactolic (−)-6,6′-dinitrohinokinin, presents in vitro and in vivo activities against Schistosomamansoni. Here, we identified changes in the protein expression after exposure to dibenzylbutyrolac-tolic (−)-6,6′-dinitrohinokinin. We applied two-dimensional gel electrophoresis (2-DE) to S. mansonisoluble protein extracts and observed at least 38 spots to be affected by dibenzylbutyrolactolic (−)-6,6′-dinitrohinokinin. We further identified 25 differentially expressed proteins by mass spectrometry.Enrichment for biological processes and predictive analyses of protein-protein interactions suggest thatdibenzylbutyrolactolic (−)-6,6′-dinitrohinokinin targets proteins involved mainly in metabolic processes,especially carbohydrate metabolism. In summary, this study provides an interesting approach to under-stand the anti-parasitic activity of semi-synthetic (−)-6,6′-dinitrohinokinin a derivative compound fromlignan and for the development of new therapy strategies.
Keywords: (−)-6;6’-dinitrohinokinin; Lignan; Mass spectrometry; Proteome; Schistosoma mansoni; Two-dimensional gel electrophoresis